Assessing the Impact of Government Initiatives on Primary Education Access and Quality in Bangladesh (1971-2000) - Masum, Md Abdullah Al (International Journal of Asian Education, 2025)
The period from 1971 to 2000 represents a transformative era for primary education in Bangladesh, driven by post-independence reforms and the government’s commitment to universal education. This study critically examines government-led initiatives aimed at improving access to and the quality of primary education. Key programs analyzed include the Universal Primary Education initiative, the Primary Education Development Program (PEDP I), and conditional cash transfer schemes such as Food for Education (FFE) and the Female Secondary Stipend Program (FSSP). Employing a policy analysis framework, the study evaluates the design, implementation, and long-term impacts of these initiatives. Findings reveal notable progress in primary education enrollment, with rates increasing from 75.6% in 1991 to 96.6% in 2000. Gender disparities also narrowed significantly, achieving near parity in primary school enrollment by the end of the decade. Despite these achievements, the education sector faced persistent challenges, including high dropout rates, insufficient teacher training, overcrowded classrooms, and systemic resource mismanagement. Political interference and bureaucratic inefficiencies further hindered the effective implementation of educational policies. This study highlights the dual nature of Bangladesh’s educational progress: while access to primary education has expanded considerably, issues related to the quality of instruction, curriculum relevance, and equitable resource distribution remain unresolved. The findings underscore the need for a more integrated approach to policy implementation, focusing not only on enrollment but also on educational outcomes and sustainability. These insights offer valuable guidance for future policy reforms aimed at achieving universal access to high-quality primary education in Bangladesh.